Klasifikasi Dan Pemetaan Famili Tanah Berdasarkan Sistem Taksonomi Tanah di Desa Penatih Dangin Puri Kecamatan Denpasar Timur - IDA AYU SRI MAS ARY SUSANTHI; I MADE MEGA; KETUT SARDIANA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2014)
ABSTRACT Classification and Mapping of Soil Family Based on Soil Taxonomy System at Penatih Dangin Puri Village, District of East Denpasar. The research at Penatih Dangin Puri Village, aims to classify and mapping the soil at Penatih Dangin Puri Village based on Soil Taxonomy System up to soil family category. This research was using soil survey method at the field to observed soil morphology, soil test at laboratory for the properties of physical, chemical, and clay fraction mineralogy. Soil classification was conducted until soil family category, semi detailed soil mapping with the scale of 1 : 25.000. The result of soil classification showed that the soil at Penatih Dangin Puri Village is classified into the order of Inceptisol and Mollisols, sub-order of Aquepts and Udolls, great group of Epiaquepts and Hapludolls, sub-group of Typic Epiaquepts, Typic Hapludolls, and Aeric Epiaquepts, family of Typic Epiaquepts, very fine, mixed, isohyperthermic; Typic Hapludolls, fine, mixed, isohyperthermic and Aeric Epiaquepts, fine-loamy, mixed, isohyperthermic. Semi detailed soil mapping with the scale of 1: 25.000 at Penatih Dangin Puri Village generates 5 SPT (Soil Mapping Unit), namely: 1) Association of Typic Epiaquepts, very fine, mixed, isohyperthermic with Aeric Epiaquepts, fine-loamy, mixed, isohyperthermic; 2) Typic Epiaquepts, very fine, mixed, isohyperthermic; 3) Typic Hapludolls, fine, mixed, isohyperthermic; 4) Typic Hapludolls, fine, mixed, isohyperthermic; and 5) Typic Hapludolls, fine, mixed, isohyperthermic. Keywords: soil classification, soil mapping, penatih dangin puri village